(untitled) (Proceedings of Southern Federal University. Philology, 2014)
Key words: conceptual space “society”, economical, social, political, spiritual spheres, sociolinguisms, sociolinguistic antonyms. The article touches upon the processes of conceptualization and categorization. The author describes the basic notions of the conceptual space “society” and points out the fundamental spheres of society, such as social, economic, political and spiritual ones. The author also carries out semantic classification of sociolinguisms. This term was introduced by professor Boeva-Omelechko and represents the notions of conceptual space “society”. The linguistic peculiarities of these words are also analyzed in the article. Balashenko Natalia Andreevna - post-graduate student of theory and practice of the English language dpt.